The neuroterrain 3D mouse brain atlas - Bertrand, Louise; Nissanov, Jonathan (Frontiers in Neuroinformatics, 2008)
A significant objective of neuroinformatics is the construction of tools to readily access, search, and analyze ana-tomical imagery. This goal can be subdivided into development of the necessary databases and of the computer vision tools for image analysis. When considering mesoscale images, the latter tools can be further divided into registration algorithms and anatomical models. The models are atlases that contain both bitmap images and tem-plates of anatomical boundaries. We report here on construction of such a model for the C57BL/6J mouse. The intended purpose of this atlas is to aid in automated delineation of the Mouse Brain Library, a database of brain his-tological images of importance to neurogenetic research.